State Separation for Code-Based Game-Playing Proofs - Brzuska, Chris; Delignat-Lavaud, Antoine; Fournet, Cédric; Kohbrok, Konrad; Kohlweiss, Markulf (Asiacrypt, 2018)
The security analysis of real-world protocols involves reduction steps that are conceptually simple but still have to account for many protocol complications found in standards and implementations. Taking inspiration from universal composability, abstract cryptography, process algebras, and type-based verification frameworks, we propose a method to simplify large reductions, avoid mistakes in carrying them out, and obtain concise security statements. Our method decomposes monolithic games into collections of stateful packages representing collections of oracles that call one another using well-defined interfaces. Every component scheme yields a pair of a real and an ideal package. In security proofs, we then successively replace each real package with its ideal counterpart, treating the other packages as the reduction. We build this reduction by applying a number of algebraic operations on packages justified by their state separation. Our method handles reductions that emulate the game perfectly, and leaves more complex arguments to existing game-based proof techniques such as the code-based analysis suggested by Bellare and Rogaway. It also facilitates computer-aided proofs, inasmuch as the perfect reductions steps can be automatically discharged by proof assistants. We illustrate our method on two generic composition proofs: (1) a proof of selfcomposition using a hybrid argument; and (2) the composition of keying and keyed components. For concreteness, we apply them to the KEM-DEM proof of hybridencryption by Cramer and Shoup and to the composition of forward-secure game-based key exchange protocols with symmetric-key protocols.